THE DEVELOPMENT OF ENVIRONMENT INSTRUCTIONAL MEDIA TO INCREASE THE STUDENT’S RESPONSIBILITY IN ELEMENTARY SCHOOL OF FLOODING PROBLEMS - Masitah -; Sonja VT Lumowa; Richart Singal (PROSIDING SEMINAR KIMIA, 2015)
The development of environment instructional media to increase the student’s responsibility of flooding problems which happen in Samarinda East Kalimantan. It is necessary because of flooding is a problem that is very common in Samarinda,The Student’s in Elementary School must have a responsibility early because of that it is important to development an instructional media which can make the right responsibility for this problem, in the second year of this research have the aim to know the effectivity of this media. There are two class, the first class is control and the other is experimental class with have the same ability, from the result of t - test we know that the probability of t -test is less than 0.05 it’s mean that there are the difference between control class and experiment class which instructional media used. The conclusion of this research is this instructional media have the effectivity for increase the responsibility of flooding problems